#MacroMesoMicro: Systemic territory framework from the perspective of social innovation - Calzada, I; Chautón, A; Siena, D (Urbano Humano, 2013)
The place matters. We were born there, have been living and working there, entered there and exited from there. Places are an object of observation from the outside while we experience them from the inside. A place is the most ethnographic level of observation of relational territorialisation. However, do we really know how territories behave? Can we really observe in practise the notion of the Network Territory? How does the dynamic concept of a territory fit and juxtapose with that of a network? Some territories are putting all their efforts, thanks to the common work of public, private, and civil agents, into restructuring the post-crisis economic and social system. Nevertheless, can we observe and see what is occurring in these places and territories? How are we supposed to observe those big black boxes with input and output but with an unknown and hardly explainable process? How can we apply hermeneutics to the socially innovating processes in the networked territories at any scale? What tools should we use for this observation? What tools do we want and can we use to intervene? What effect do we ultimately want to have? All these elements may demand a systemic vision in the cybernetic multi-disciplinary sense that Social Innovation requires and that links with the two main currents of Social Innovation in a coherent way: we are referring to, on the one hand, the more academic approach, with a social justice dimension, aligned towards the Territory and Social Economy and, on the other hand, the more practitioner and policy-making approach, championed by the third-way labour school of thought of the Young Foundation, Nesta and Demos.